CONTEMPORARY APPROACHES TO MODERNIZATION IN ASIAN AND EASTERN COUNTRIES - Bakhtiyor Omonov (Bright Mind Publishing, 2025)
This article analyzes the evolution of “economic miracles” and the process of political modernization in the countries of Southeast Asia (China, Japan, India, Turkey, etc.), and conclusions based on scientific analysis are given. Foreign experience is a good study for scientists, economists and politicians of the CIS member states.
Keywords: Society, modernization, southeast Asia, economic miracle, development concept, model, main features and distinctive aspects of modernization, Japanese Spirit-Western technologies, a system of behavior, Western technologies and Indian society, Asian values.